Hak Restitusi Korban Tindak Pidana Perdagangan âOrang Perspektif Hukum Pidana Islam - Pramugarini, Yushinta (Al-Jinayah: Jurnal Hukum Pidana Islam, 2016)
Abstract: This article discusses the analysis of Islamic criminal law on restitution rights of victims of human trafficking crime. The provisions concerning the restitution of human trafficking crime have been defined in article 48 paragraph 2 No. 21 of 2007 on the Eradication of Trafficking in Persons. Understanding restitution according to Law No. 21 of 2007 on the Eradication of Trafficking in Persons is the payment of compensation charged to the offender by a court decision which is legally binding on the material loss and/or immaterial suffered by the victim or the descendent.Â  In an Islamic criminal law, the perpetrators of criminal acts of trafficking in persons also have in common or equally punishable by cumulative. Cumulative punishment under Islamic criminal law,Â  in the form of sanctions, is taâzir reinforced or exacerbated by diyat (fine).Keywords: Islamic criminal law, restitution rights, trafficking in persons.Â Abstrak: Artikel ini membahas tentang analisis hukum pidana Islam terhadap hak restitusi korban tindak pidana perdagangan orang. Ketentuan mengenai restitusi tindak pidana perdagangan orang telah dirumuskan dalam pasal 48 ayat 2 No. 21 Tahun 2007 tentang Pemberantasan Tindak Perdagangan Orang. Pengertian restitusi menurut Undang-Undang No.21 tahun 2007 tentang Pemberantasan Tindak Pidana Perdagangan Orang adalah pembayaran ganti kerugian yang dibebankan kepada pelaku berdasarkan putusan pengadilan yang berkekuatan hukum tetap atas kerugian materil dan/atau immateril yang diderita korban atau ahli warisnya. Dalam hukum pidana Islam, bagi pelaku tindak pidana perdagangan orang juga terdapat kesamaan atau sama-sama dihukum dengan hukuman kumulatif. Hukuman kumulatif dalam hukum pidana Islam, yaitu berupa sanksi taâzÃ®r yang diperkuat atau diperberat dengan diyat (denda).Kata Kunci: Hukum pidana Islam, hak restitusi, perdagangan orang.